Ht-El System In Realizing The Escalation Of Electronic Certificates With Legal Certainty (Study Of The Land Office Of Karanganyar Regency) - Aziz Zaelani, Muhammad; Rudatyo, Rudatyo (International Journal of Educational Research & Social Sciences, 2022)
This research addresses the following topics: (i) the implementation of the HT-el system at the Karanganyar Regency Land Office; and (ii) legal issues encountered while implementing the HT-el system at the Karanganyar Regency Land Office. This empirical study expands on describing the policy approach as well as micro-interactional effects. The research's findings are: First, the Karanganyar Regency Land Office implemented the HT-el system in accordance with Minister of ATR/BPN Regulation Number 5 of 2020, with empirical evidence of data recapitulation of the number of HT-el applications for the 2020 and 2021 periods, accompanied by risk management analysis. Second, the legal issues of implementing the HT-el system at the Karanganyar Regency Land Office include the substantive issue of a lack of implementing regulations as implementing guidelines and implementation parameters, the issue of structural apparatus lack of human resources overcoming network error problems, budgeting for repair and maintenance as the primary means of HT-el services, and socio-cultural issues; the public's lack of enthusiasm due to a lack of socialization and assistance regarding the ease of HT-el services. Suggestions for research include the Ministry of ATR/BPN issuing implementing regulations that accommodate the standardization parameters for the implementation of the HT-el system in the region, as well as the Head and Employees of the Land Office of Karanganyar Regency increasing socialization and assistance in the use of HT-el services and systems to the community, as well as employee training in overcoming network problems.